Magnetic resonance imaging of cervical carcinoma using an endorectal surface coil - Brocker, Kerstin A.; Sohn, Christof (European journal of radiology, 2014)
Introduction - The objective of this trial is to investigate the diagnostic value of magnetic resonance imaging (MRI) with an endorectal surface coil for precise local staging of patients with histologically proven cervical cancer by comparing the radiological, clinical, and histological results. - Materials and methods - Women with cervical cancer were recruited for this trial between February 2007, and September 2010. All the patients were clinically staged according to the FIGO classification and underwent radiological staging by MRI that employed an endorectal surface coil. The staging results after surgery were compared to histopathology in all the operable patients. - Results - A total of 74 consecutive patients were included in the trial. Forty-four (59.5%) patients underwent primary surgery, whereas 30 (40.5%) patients were inoperable according to FIGO and underwent primary radiochemotherapy. The mean age of the patients was 50.6 years. In 11 out of the 44 patients concordant staging results were obtained by all three staging modalities. Thirty-two of the 44 patients were concordantly staged by FIGO and histopathological examination, while only 16 were concordantly staged by eMRI and histopathological examination. eMRI overstaged tumors in 14 cases and understaged them in 7 cases. - Conclusions - eMRI is applicable in patients with cervical cancer, yet of no benefit than staging with FIGO or standard pelvic MRI. The most precise preoperative staging procedure still appears to be the clinical examination.
Gesehen am 20.08.2020